2013
DOI: 10.1161/jaha.113.000478
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐Two‐Year Population Trends in Sodium and Potassium Consumption: The Minnesota Heart Survey

Abstract: BackgroundLimiting dietary sodium consumption is a core lifestyle recommendation for the prevention of hypertension. There is increasing evidence that low potassium consumption also increases hypertension risk. We estimated sex‐specific 22‐year trends in sodium and potassium consumption.Methods and ResultsWe used data from the Minnesota Heart Survey, which performs surveillance of risk factors for cardiovascular disease in the Minneapolis–St. Paul metropolitan area. The Minnesota Heart Survey is a random popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…We do not have available the individual sodium intake in our population, but recent studies have reported that the average dietary sodium intake in Minnesotans is unchanged over the past 2 decades and still exceeds the recommended upper limit of 2300 mg/day. 33 Further, about 90% of subjects in our cohort were Caucasian, 4% were Asian, 3% African-American, and 3% Hispanic. 34 Thus our findings may not be completely relevant to other ethnic groups other than Caucasians, although Musani et al have recently reported that higher aldosterone level predicts incident MetS in African-Americans.…”
Section: Discussionmentioning
confidence: 67%
“…We do not have available the individual sodium intake in our population, but recent studies have reported that the average dietary sodium intake in Minnesotans is unchanged over the past 2 decades and still exceeds the recommended upper limit of 2300 mg/day. 33 Further, about 90% of subjects in our cohort were Caucasian, 4% were Asian, 3% African-American, and 3% Hispanic. 34 Thus our findings may not be completely relevant to other ethnic groups other than Caucasians, although Musani et al have recently reported that higher aldosterone level predicts incident MetS in African-Americans.…”
Section: Discussionmentioning
confidence: 67%
“…The remainder, however, should still be elucidated. We have no data on trends in the salt content in food or sodium excreted in urine over time, but as in other countries, 36 high levels are observed currently in Spain. 37 Moreover, the diet of hypertensive patients in Spain, including older individuals, has a low accordance with the Dietary Approaches to Stop Hypertension (DASH) and Mediterranean dietary pattern, including sodium intake, 37 which may be counterbalancing efforts in drug treatment.…”
Section: Explanations For Changes In Hypertension Controlmentioning
confidence: 80%
“…Moreover, salt intake plays an important role in the aldosterone-mediated organ damage. Common in U.S. society as well as in Minnesota 24 , high salt diet can potentiate the negative effects of aldosterone via activation of the Rho family member Rac1 25 . Importantly, in Yanomamo Indians, very low salt intake is characterized by high plasma renin and aldosterone levels without the presence of CV disease 26 .…”
Section: Discussionmentioning
confidence: 99%